Dissolving efficacy of some organic solvents on gutta-percha Eficácia dissolvente de alguns solventes orgânicos sobre a guta-percha - Bianca Silva Magalhães; Julia Elis Johann; Rafael Guerra Lund; Josué Martos; Francisco Augusto Burkert Del Pino (Sociedade Brasileira de Pesquisa Odontológica, 2007)
The aim of this study was to evaluate the solubility of gutta-percha in four organic solvents used in endodontics. The solubility of gutta-percha (Dentsply) was assessed in xylol, orange oil, eucalyptol, chloroform and distilled water. A hundred and fifty samples of gutta-percha were prepared using a standardized stainless steel mould and divided into five groups for immersion in the different solvents tested and in distilled water (control group) for 2, 5 and 10 minutes. The means of gutta-percha dissolution in the solvents were obtained by the difference between the pre-immersion original weight and the post-immersion weight in a digital analytical scale (Gehaka - AG2000). Data were statistically analyzed by Analysis of Variance (ANOVA) and multiple comparisons with Scheffe's test (p < 0.05). The best solvency capacity was obtained with xylol. Chloroform, orange oil and eucalyptol presented similar results, and distilled water did not promote alterations in the gutta-percha. O presente estudo avaliou a solubilidade da guta-percha em quatro solventes orgânicos empregados em endodontia. A solubilidade da guta-percha (Dentsply) foi testada em xilol, óleo de laranja, eucaliptol, clorofórmio e água destilada. Foram preparadas cento e cinqüenta amostras de guta-percha por meio de uma matriz metálica que foram divididas em cinco grupos para imersão nos diferentes solventes a serem testados e na água destilada (grupo controle) durante 2, 5 e 10 minutos. As médias da dissolução da guta-percha nos diferentes solventes foram obtidas pela diferença entre o peso inicial pré-imersão e o peso pós-imersão através de uma balança analítica digital (Gehaka - AG2000). Os dados foram analisados estatisticamente através da análise de variância (ANOVA) e comparações múltiplas com teste de Scheffe's (p < 0,05). A melhor capacidade de solvência foi obtida com o xilol. Clorofórmio, óleo de laranja e eucaliptol apresentaram resultados semelhantes, e a água destilada não promoveu alterações na guta-percha.